NILAI DIAGNOSTIK ANTI DENGUE IgA DAN NS1, SERTA IgM/IgG DI INFEKSI VIRUS DENGUE (The Diagnostic Value of Anti Dengue IgA and Anti Dengue IgM/IgG in Dengue Virus Infection) - Resna Resna; Aryati Aryati; Puspa Wardhani; Erwin Triyono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
The clinical manifestations of dengue virus infection are varied and thus a specific diagnostic examination is required. Usually antidengueIgM is often used, but the presence in the circulation is 3−8 months long. NS1 is sensitive in the detection of primary infection,whereas IgG is more better used in secondary infection. The examination of anti-dengue IgA as a new marker is estimated to be ableto detect the acute primary and secondary infection, however the diagnostic value of anti-dengue IgA is not much well known for theIndonesian population. This study was done at the Tropical Infectious Disease Ward of Dr. Soetomo Hospital, Surabaya during February– April 2013. The samples consisted of 37 sera from patients infected by dengue virus and 37 sera from those non one (dengue virusinfection patients). The NS1 serum, anti-dengue IgM and anti dengue IgG were examined by ELISA and anti-dengue IgA was examined byan indirect immunochromatography method using Assure@ Dengue IgA Rapid Test (MP Biomedicals Asia Pacific Pte Ltd). The diagnosticvalue was analyzed by 2x2 table with a confidence interval of (CI) 95%. The used gold standards were from the 1997th WHO criteriaand one of the positive dengue serological tests by ELISA (NS1/anti dengue IgM/anti dengue IgG). AUC and anti-dengue IgA cut-off weredetermined by ROC curve. The Diagnostic value of anti-dengue IgA showed a sensitivity and specificity of 83.8% (67.3 to 93.2) and 81.1%(64.3 to 91.4). A positive predictive value of 81.6% (65.1 to 91.7) and a negative predictive value of 83.3% (66.5 to 93.0) was found. Thepositive likelihood ratio was 4.4 times (2.2 to 8.8) and negative likelihood ratio of only 0.2 times (0.09 to 0.42). The best cut off valueof 0.2 was shown by the area under the curve of 83.5%. Based on this study, the diagnostic value of anti-dengue IgA had a good validityfor the diagnosis of dengue virus infection.